Technology Transfer, Crop Production, and Food Security: Evidence from Vietnam’s ATDP Participation - Nguyen Anh Bo; Nguyen Van Duong; Jingbo Cui Thi Ha; Shen Lin Bo (Journal of Economics Business Industry, 2024)
This study aims to examine the causal effect of agricultural technology transfer through Vietnam’s participation in the Greater Mekong Subregion Agricultural Technology Demonstration Program (ATDP) on crop production, trade performance, and food security. Using a province-by-crop panel dataset covering 63 Vietnamese provinces, eight food crops, this study applies a triple difference-in-differences approach by comparing recipient and non-recipient provinces, demonstration and non-demonstration crops, and pre- and post-program periods. Robustness is assessed through parallel trend and event-study analyses. The results show that ATDP participation significantly increases harvest area and grain production of demonstration food crops by approximately 20.1% and 15.96%, respectively. The effect emerges around two years after implementation and remains persistent. ATDP also expands export volume and value, reduces import dependence in direction, and improves food security indicators at the provincial level. Mechanism analysis indicates that free-standing technical assistance and programs implemented by state-owned enterprises generate stronger outcomes than general grant aid. This study contributes to the literature by providing causal evidence on South-South agricultural technology cooperation using a rigorous triple DID design at the province-crop level. The findings suggest that agricultural cooperation should prioritize context-specific technical demonstration, extension training, and institutional implementation capacity. The study is limited to first-cohort ATDP provinces and selected food crops; future research should examine longer-term yield intensification, household welfare, and cross-country replication.